Phycoremediation of Rice Parboiling Industry Wastewater by Micro Algae and Utilization of Treated Water for Crop Production - Gandhi, N.; Reddy, M. Madhan Obul; Reddy, D. Madhusudhan (International Journal of Scientific Research in Biological Sciences, 2022)
The screening of freshwater microalgae which is grown in the outdoor paddy fields for phycoremediation of rice parboiling industries wastewater is investigated in the current project. Diluted sample of wastewater with distilled water in 1:1 ratio is denoted as Raw and Distilled Water (RDW) sample and diluted sample with tap water in 1:1 ratio is denoted as Raw and Tap Water (RTW) were allowed for phycoremediation. The highest growth of microalgae biomass has increased and shown great biomass in RDW sample of rice parboiling industries wastewater. At Day 15 approximately 13.72×106 cell/mL with the highest removal of nitrate nitrogen, ammonia nitrogen, total nitrogen, phosphate and total organic carbon (BOD and COD) are 82.62%, 98.23%, 87.66%, 76.26, 93.32% and 95.32% respectively. RTW wastewater was able to reach maximum growth by Day 18 where cell concentration was approximately 19.7×105 cell/mL. Significantly reduction for some nutrients such as nitrate nitrogen, ammonia nitrogen, total nitrogen, phosphate and total organic carbon (BOD and COD) were observed. These findings provide good indication of microalgae growth and phycoremediation of rice parboiling industries wastewater. The information from these findings could be of potential use for biotechnology industries, for further development of bio-based product from microalgae biomass. The current study is extended to know the impact of raw undiluted rice parboiling industries wastewater and treated i.e., phycoremediation by RDW and RTW on Bengal gram (Cicer arietinum) for germination, growth, physiological and biochemical response. Plant growth is measured using growth analysis parameters such as, % germination, germination index, mean germination time, relative growth rate (RGR), net assimilation rate (NAR), leaf area ratio (LAR), leaf weight ratio (LWR), specific leaf area (SLA), specific leaf weight (SLW), leaf area duration (LAD). The physiological response of crop irrigated with undiluted raw rice parboiling industry wastewater, treated RDW and treated RTW are calculated by measuring % phytotoxicity, % inhibition, tolerance indices, seed vigor index.